Effect of oral fluconazole 1200 mg/day on QT interval in African adults with HIV-associated cryptococcal meningitis. (24th September 2018) - Molloy, Síle F.; Bradley, John; Karunaharan, Natasha; Mputu, Muhammad; Stone, Neil; Phulusa, Jacob; Chawinga, Chimwemwe; Gaskell, Kate; Segula, Dalitso; Ming, Damien; Peirse, Mary; Chanda, Duncan; et al.
Abstract : N/A: We assessed the effect of fluconazole 1200 mg/day on the QT interval in cryptococcal meningitis patients. Mean corrected QT (QTc) change from baseline to day 7 was 10.1 ms (IQR: −28 to 46 ms) in the fluconazole treatment group and −12.6 ms (IQR: −39 to 13.5 ms) in those not taking fluconazole ( P = 0.04). No significant increase in QTc measurements over 500 ms was observed with fluconazole. Nevertheless, it remains important to correct any electrolyte imbalance and avoid concomitant drugs that may increase QTc.